Microabrasão-Corrosão de Revestimentos de Inconel 625 Depositados por Plasma Pó (PTAP) - Santos, Regina Paula Garcia (2018)
Due to its high cost, deposition of Inconel 625 onto cheaper substrates by different techniques can be an economically viable alternative. In this work, PTAP (Plasma Transferred Arc – Powder) was used to deposit Inconel 625 onto carbon steel substrates. Parameterization of the process resulted in thick deposits (> 3 mm). Current, welding speed and powder feed rate were varied within a narrow range to identify an operational envelope within which good deposits could be produced, their quality was assessed both in terms of adequate macro and microstructure. Macrographic analysis allowed the measurement of the geometric characteristics of the beads. Two groups were identified, one with lower dilution (<6%) and another with greater dilution (7.5 to 11.9%). Microhardness profiles SEM-EDX analysis and X-ray diffraction characterized the microstructure of the deposits, which exhibited dendritic microstructures. Microsegregation of Nb in the interdendritic regions resulted in the formation of eutectic phases constituted of a Ni-Cr matrix and second-phase particles rich in Nb and Mo. A fixed-sphere microabrasometer was employed to assess the abrasion resistance of the deposits, using a zirconia ball with controlled roughness (Ra between 0.32 and 0.38 μm) and a slurry with a concentration of 20% of SiO2 particles. The tribological conditions used in the microabrasion tests resulted in mixed wear mechanisms, involving predominantly sliding but also rolling of the abrasive particles. No effect of the dilution of the deposits on their abrasion resistance was found. To evaluate their corrosion resistance, potentiodynamic tests were carried out using 3.5% NaCl, NaCl + FeCl3 and NaCl + H2SO4 solutions. The H2SO4 solution showed to be the most aggressive, for which it was possible to identify variations in current density between the groups with different dilutions, whereas no significant differences were identified for the other electrochemical variables. For the microabrasion-corrosion, the slurries contained SiO2 particles added to the same solutions used in the corrosion tests. The wear coefficients measured under microabrasion-corrosion conditions were higher than under pure microabrasion conditions, evidencing a positive synergy between microabrasion and corrosion. On the other hand, the friction coefficients reduced when compared with pure microabrasion for all the slurries tested, suggesting that the corrosion products form a film with relatively low friction coefficient. Besides, for the slurry containing the most aggressive solution (NaCl + H2SO4), there was a small effect of dilution on the electrochemical variables, where the deposits with higher dilution showed a current density greater than the group with the lowest dilution (which characterizes the lower corrosion resistance of this group).